Knowledge, attitude, and practice about antimicrobial stewardship concepts among practitioners - Bodke, Akshay Vishwasrao; Mujeeb, Momin Mohd Abdul; Pardeshi, Milind L.; Dabhade, Sangeeta S.; Tiwari, Smita A.; Gawari, Nitin C.; Jadhav, Amol R.; Kedare, Rahul V. (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Antimicrobial agents have been crucial in human medicine for over five decades. However, antimicrobial resistance (AMR) has become a significant global threat, with the world health organization (WHO) identifying it as a top ten health threat in 2019. Over 50% of antimicrobials are improperly used, leading to increased morbidity, mortality, and healthcare costs. This study assesses the knowledge, attitudes, and practices (KAP) of physicians regarding AMR to enhance antimicrobial stewardship (AMS). Methods: A cross-sectional, descriptive study was conducted among physicians in Maharashtra, India, from December 2023 to March 2024. A self-administered survey, developed through literature review and pilot testing, was distributed electronically. The questionnaire included 27 questions across three sections: knowledge, attitude, and practice. Responses were collected anonymously. Results: Out of 580 responses, 72% of participants were aware of AMS, with an average knowledge score of 7.3 out of 11. High awareness was noted, with 96% correctly identifying the primary goal of AMS. However, only 31.6% consistently documented the rationale for prescriptions, and 80.3% de-escalated from broad-spectrum to narrow-spectrum antimicrobials based on culture results. Conclusions: While foundational knowledge and positive attitudes towards AMS were strong, variability in practices highlighted the need for ongoing education and system improvements. Gaps in specific knowledge areas and mixed attitudes towards newer antimicrobials and long-duration antimicrobial use indicate the need for consistent guidelines and education. Improving documentation practices, updating resistance patterns, and enhancing trust in laboratory results are crucial for optimizing AMS. Further research should address the influence of physicians’ specialties, hospital types, and years of experience on prescribing behaviors.